Android platform to find blood donors and predicting most suitable donors - Ahmed, Nakib; Rashid, Safoan Bin; Moury, Sharmin Sultana; Nahar, Ankur (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.